2023
DOI: 10.1503/cjs.018121
|View full text |Cite
|
Sign up to set email alerts
|

Use of multidisciplinary positive deviance seminars to improve efficiency in a high-volume arthroplasty practice: a pilot study

Abstract: Background: Positive deviance (PD) seminars, which have shown excellent results in improving the quality of surgical practices, use individual performance feedback to identify team members who outperform their peers; the strategies from those with exemplary performance are used to improve team members' practices. Our study aimed to use the PD approach with arthroplasty surgeons and nurses to identify multi disciplinary strategies and recommendations to improve operating room (OR) efficiency. Methods:We recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In six articles, the criteria for the selection of PDs were unclear or unspecified [ 39 , 47 , 50 , 76 , 143 , 145 ] and in the remaining papers, the selection of PDs does not apply as they are systematic reviews [ 20 , 57 , 59 , 63 ] and adoption program papers that are implemented based on best practices identified from other positive deviant practices [ 28 , 51 , 54 , 67 , 92 , 119 ]. However, performance-based criteria have been used to identify PDs at individual, health facility or health system levels in majority of the articles [ 11 , 23 , 24 , 26 , 27 , 30 , 32 , 33 , 35 38 , 40 46 , 48 , 53 , 55 , 56 , 60 62 , 65 , 66 , 68 – 75 , 77 , 78 , 80 – 88 , 90 , 93 , 95 97 , 99 – 105 , 107 – 118 , 121 , 122 , 124 142 , 144 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In six articles, the criteria for the selection of PDs were unclear or unspecified [ 39 , 47 , 50 , 76 , 143 , 145 ] and in the remaining papers, the selection of PDs does not apply as they are systematic reviews [ 20 , 57 , 59 , 63 ] and adoption program papers that are implemented based on best practices identified from other positive deviant practices [ 28 , 51 , 54 , 67 , 92 , 119 ]. However, performance-based criteria have been used to identify PDs at individual, health facility or health system levels in majority of the articles [ 11 , 23 , 24 , 26 , 27 , 30 , 32 , 33 , 35 38 , 40 46 , 48 , 53 , 55 , 56 , 60 62 , 65 , 66 , 68 – 75 , 77 , 78 , 80 – 88 , 90 , 93 , 95 97 , 99 – 105 , 107 – 118 , 121 , 122 , 124 142 , 144 ].…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing the PD approach in healthcare safety and quality programs has led to huge time and cost savings. For instance, Gold R, et al (2023) revealed that the application of the PD approach has resulted in great improvements in time management in surgical cases across all time intervals of procedures with an overall time of 49.84 min saved per day compared to the baseline values [ 32 ]. Similarly, an improvement in operating room time management after successive value improvement initiatives has also been reported [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations